Factors Associated With The Incidence Of Bronchitis In Rsud Rupit North Musi Rawas District - Amin, Muhammad All; Samidah, Ida; Surahman, Feri; Darmawansyah, Darmawansyah; Habibi, Julius (Journal of International Public Health, 2023)
Bronchitis is an airway disease that is often found in the community and is a health problem because of its chronic, persistent, and progressive nature (Soegito, 2020). Bronchitis cases in 2022 increased very rapidly from no previous cases to 136 cases. (Rupit Hospital, 2022). The purpose of the study was to determine the factors associated with the incidence of bronchitis at the Rupit Regional General Hospital, North Musi Rawas Regency. This study is a quantitative study using a cross sectional design. The research sample was 69 respondents. Data analysis was performed with the chi-square test with a significance level of 95% using SPSS 16 software. The results of univariate analysis showed, 20 (29.0%) respondents smoked ≥20 btg/per day, 16 (23.2%) respondents had risky jobs and had respondents who had a family history of 21 people (30.4%). The results of bivariate analysis showed there was a significant relationship between smoking habits Value p = 0.000. Occupation Value p = 0.038 and Family History Value p = 0.033 with the incidence of Bronchitis < α - 0.05 at the Rupit Regional General Hospital, North Musi Rawas Regency in 2023. It is hoped that the Rupit Regional General Hospital of Musi Rawas Regency will always improve services in order to achieve patient satisfaction. Hospitals have an obligation to ensure that patients are satisfied with the health services that have been provided and ensure that all health workers have provided what patients are entitled to.